Gimnazjalista czyta Redutę Ordona. O utworach z kontekstem historycznym w kształceniu polonistycznym - Horwath, Ewa (Postscriptum Polonistyczne, 2020)
The article raises an issue of students’ cognition of literary texts from the nineteenth century included in the core curriculum. The author draws attention to the difficulties associated with understanding the literal and metaphorical language that varies from the everyday language of the students. The author also introduces methods to mitigate these problems and proposes a form of classroom exercises which facilitate the analysis and interpretations of literary works.